Otto Bauer (1881-1938) Thinker and Politician - Czerwinska-Schupp, Ewa (Brill, 2016)
This work depicts Otto Bauer as the main politician of the SDAP and attempts a critical-analytical interpretation of his socio-political theories, which are shown against the background of the debates within the First and Second Internationals, political events within the SDAP, the international workers' movement, and the socio-historical processes in Austria and Europe at the time.